PENINGKATAN KREATIVITAS MELALUI AKTIVITAS MENGGAMBAR PADA ANAK USIA 5-6 TAHUN - ROKYAL HARJANTY (JUPE : Jurnal Pendidikan Mandala, 2019)
This research is motivated by the participation that requires in the process of learning activities in RA Barokatus Shaulatiyah, NW Puyung namely the level of children's creativity is still low. Children are still not able to develop ideas and imagination that children have. In the learning process the teacher is more dominated by counting, memorizing and reading. In the learning process in the classroom have not used appropriate learning methods and strategies, such as explaining how or methods to color that must be done. So that children become less interested, feel bored and lazy to color. The purpose of this study is to improve the creativity of young children and the quality of learning through coloring activities in children in RA Barokatus Shaulatiyah NW Puyung in 2019/2020 Academic Year. This type of research is Classroom Action Research. This research was conducted in 2 cycles consisting of 3 times at the meeting each cycle. Subjects in this study were class B with a total of 15 students consisting of 9 girls and 6 boys. Data collection is done by observation sheets in the learning process, which is to find out the increase in early childhood creativity. The results showed that the children's creativity was indicated by the achievement of the creativity score before the action was reached 20%, increased to 60% in the first cycle of action, and increased to 92, 5% in the second cycle of action.